Focused ultrasound thalamotomy for multiple sclerosis–associated tremor. (June 2020) - Máñez-Miró, Jorge U; Martínez-Fernández, Raúl; del Alamo, Marta; Pineda-Pardo, José A; Fernández-Rodríguez, Beatriz; Alonso-Frech, Fernando; Álvarez-Cermeño, Jose Carlos; Obeso, José A
Multiple sclerosis (MS)-related tremor is frequent and can often be refractory to medical treatment, which makes it a potential source of major disability. Functional neurosurgery approaches such as thalamic deep brain stimulation (DBS) or radiofrequency thalamotomy are proven to be effective, but the application of invasive techniques in MS tremor has so far been limited. Magnetic resonance (MR)-guided focused ultrasound thalamotomy, which has already been approved for treating essential and parkinsonian tremor, provides a minimally invasive approach that could be useful in the management of MS tremor. We report for the first time a patient with medically refractory MS-associated tremor successfully treated by focused ultrasound thalamotomy.